1984
DOI: 10.1021/bi00301a043
|View full text |Cite
|
Sign up to set email alerts
|

Reductive activation of phenylalanine hydroxylase and its effect on the redox state of the non-heme iron

Abstract: Phenylalanine hydroxylase undergoes an obligatory prereduction step in order to become catalytically active as shown by stopped-flow kinetics and by measuring tyrosine formation at limiting 6-methyltetrahydropterin levels. This initial step requires oxygen and involves conversion of 6-methyltetrahydropterin directly to the quinonoid form with or without phenylalanine. The EPR spectrum of the resting enzyme (geff = 9.4-8.7, 4.3 and geff = 6.7, 5.4) is consistent with two species possessing distinctively differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 35 publications
8
118
1
Order By: Relevance
“…Since these effects were not observed on the apoenzyme or enzyme prepared with either Zn(I1) or Co(Il), they can probably be explained by a change in the redox state of the enzyme-bound iron [27]. These effects are qualitatively similar to the effects reported for rat liver phenylalanine hydroxylase [28] and rat pheochromocytoma tyrosine hydroxylase [27], although much less pronounced. Since tyrosine hydroxylase and phenylalanine hydroxylase contain tryptophan residues at similar positions, these differences may reflect differences in iron-binding sites or the initial redox state of the iron in the two enzymes.…”
Section: Quenching Of Tyrosine Hydroxylase Fluorescence By Added Metasupporting
confidence: 65%
“…Since these effects were not observed on the apoenzyme or enzyme prepared with either Zn(I1) or Co(Il), they can probably be explained by a change in the redox state of the enzyme-bound iron [27]. These effects are qualitatively similar to the effects reported for rat liver phenylalanine hydroxylase [28] and rat pheochromocytoma tyrosine hydroxylase [27], although much less pronounced. Since tyrosine hydroxylase and phenylalanine hydroxylase contain tryptophan residues at similar positions, these differences may reflect differences in iron-binding sites or the initial redox state of the iron in the two enzymes.…”
Section: Quenching Of Tyrosine Hydroxylase Fluorescence By Added Metasupporting
confidence: 65%
“…Only three other enzymes that contain monomeric iron sites, phenylalanine monooxygenase (25), superoxide dismutase (8,70), and nitrile hydratase (31,67), are known to exist. The latter two enzymes and intradiol-type catecholic dioxygenases (37) contain a ferric center, while extradiol dioxygenases (76), lipoxygenases (17), phenylalanine monooxygenase (72), and ADH of Z. mobilis (6,69) contain high-spin ) and the dithionitereduced enzyme (predominantly Fe 2ϩ ) were equally active. The weak visible absorption of pure ADH presumably arises from the ferric form of the enzyme (17,37,46).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that DTT played a mechanistic role in addition to recycling the oxidized pterin to its reduced state during the catalytic turnover. Reductive activation by a cofactor or dithionite to form the catalytically active enzyme species was reported for the phenylalanine hydroxylase from rat liver (24,25). Spectroscopic studies linked the reductive activation to the conversion of iron bound to the enzyme from Fe(III) to Fe(II) (25).…”
Section: Role Of Iron In the Reaction Of Phenylalanine Hydroxylasementioning
confidence: 97%